MENINGKATKAN KESETIAAN PELANGGAN LEWAT CUSTOMER RELATIONSHIP MANAGEMENT - Borolla, Johanis Darwin (potensio, 2009)
The maximization of customer satisfaction nowadays cannotbe fulfill only by price strategy and product quality. Somenew approaches can be implemented as a solution. One ofthese approaches is Customer Relationship Management(CRM). CRM used by company to increase customersatisfaction and loyalty by giving easier informationaccessibility and create a new relationship which is moreintense and more personal, also to build customer’s trustthrough added more services to the customer. This idea iswell-applied because it supported by information technologywhich can help in storing and classifying the information (datawarehousing), or to track and get the data in details:economic,demography, lifestyle, physiography, and more interactiveelements of the customer. Commonly, if CRM is well-applied,the information (data) of customer interaction will be recordedin details. Hence, this approach will assist the company indeveloping more ideas in order to give products and serviceswhich are more suitable to the customer’s needs, and themost important is to fulfill the customer’s satisfaction.Key word: Customer Relationship Management,customers satisfaction, customers loyalty